Combating Physician Burnout : a Guide for Psychiatrists. - LoboPrabhu, Sheila (American Psychiatric Association Publishing, 2019)
"Combating Physician Burnout: A Guide for Psychiatrists aims to educate psychiatrists about three key concepts: stress, burnout, and physician impairment. Five sections lay out the scope of the challenge and outline potential interventions. The introduction discusses the history and social context of burnout and provides psychiatrists who may be struggling with burnout with much-needed perspective. Subsequent sections discuss the potential effects of burnout on clinical care, contextual elements that may contribute to burnout, potential systemic and individual interventions, and the moral challenge burnout poses to psychiatry"--